2018
DOI: 10.26717/bjstr.2018.03.000942
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemistry of Catalase Immobilized at Polymerized-SnO2 Multiporous Modified Electrode for an Amperometric H2O2 Biosensor

Abstract: A novel amperometric H 2 O 2 biosensor based on immobilization of catalase with polymerized MPNFs of SnO 2 onto glassy carbon electrode with chitosan have been proposed in this work. Multiporous nanofibers of SnO 2 were synthesized by electrospinning method from the tin precursor by controlling the concentration followed by polymerized with aniline. Catalase was then co-immobilized with the polymerized nanofibers on the surface of glassy carbon electrode by using chitosan. The polymerized MPNFs of SnO 2 play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For the last 10 to 15 years, nanostructured electrodes have been recurrently used in the construction of third-generation catalase biosensors. This is in line with development of electrochemical biosensor in general and is justified by the advantages that carbon and metal nanomaterials provide in terms of biocompatibility, high conductivity, and large surface area [119,120,122,[193][194][195]. Quantification of H 2 O 2 and nitrite has been achieved with a catalase/NiO NPs biosensor prepared by electrodeposition of enzyme and the NPs on GC and ITO electrodes.…”
Section: Catalasesmentioning
confidence: 71%
See 1 more Smart Citation
“…For the last 10 to 15 years, nanostructured electrodes have been recurrently used in the construction of third-generation catalase biosensors. This is in line with development of electrochemical biosensor in general and is justified by the advantages that carbon and metal nanomaterials provide in terms of biocompatibility, high conductivity, and large surface area [119,120,122,[193][194][195]. Quantification of H 2 O 2 and nitrite has been achieved with a catalase/NiO NPs biosensor prepared by electrodeposition of enzyme and the NPs on GC and ITO electrodes.…”
Section: Catalasesmentioning
confidence: 71%
“…Composite materials based on surfactants, polymers, and ILs are often used to facilitate the dispersion of the nanomaterials, improve enzyme retention on the electrode, and help preserve the native conformation of the catalyst. To that end, catalase has been (i) adsorbed on GC surfaces modified with poly-L-lysine/MWCNT and 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM]BF 4 )-IL/MWCNT-NH 2 films [121,122], (ii) co-deposited with mixtures of dodecyltrimethyl ammonium bromide (DTAB)/MWCNT [195], Nafion/MWCNT-COOH [196], or chitosan/SnO 2 nanofibers/PANI on GC electrodes [194], and (iii) incorporated into multilayered assemblies with amine terminated IL (NH 2 -IL) prepared on titanium nitride (TiN) modified GC electrodes [120]. FTIR and UV-Visible spectra of the catalase/poly-Llysine/MWCNT and catalase/NH 2 -IL/TiN films indicated that the enzyme was intact upon immobilization, suggesting suitable microenvironments for catalase activity [120,122].…”
Section: Catalasesmentioning
confidence: 99%
“…14,15 In the realm of biosensors, the use of catalase (CAT) for H 2 O 2 detection is preferred, as it facilitates a direct redox reaction between CAT and the electrode. 16 Conversely, HRP has deepseated reaction centers, due to which redox mediators such as ferrocene, potassium hexacyanoferrate, catechol and methylene need to be used for better electrical wiring 17 and yet the results have been far from satisfactory. 18 Additionally, the properties and performance of the H 2 O 2 biosensor are markedly contingent upon the type of matrix used for immobilizing the enzyme.…”
Section: Introductionmentioning
confidence: 99%